A 6-month-old boy presented with progressive jaundice, dark urine and generalized pruritus for one month - Akter, Hazera; Mojumder, Md. Wahiduzzaman; Karim, A. S. M. Bazlul; Kamal, Mohammed; Nahar, Kamrun; Benzamin, Md. (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
This article has no abstract. The first 100 words appear below: A 6-month-old boy of non-consanguineous parents admitted to the Department of Pediatric Gastroenterology with the complaints of progressive jaundice, dark urine and generalized pruritus for one month. The boy was well up to five months of age. Then he developed jaundice which was progressive in nature with intermittent pale colored stool along with dark urine. His mother also complaints for generalized pruritus which was severe in intensity (disturbing sleep and daily activities) without any diurnal variations. There was no history of sib death or family history of a similar type of illness.